1995
DOI: 10.1007/bf01231444
|View full text |Cite
|
Sign up to set email alerts
|

Noncommutative graded domains with quadratic growth

Abstract: Contents o. Introduction 1. The graded quotient ring of a graded prime ring of dimension two 2. The associated divisors 3. The stable image of the curve 4. Domains of dimension two which are generated in degree one 5. The case of an automorphism of infinite order 6. Applications to the structure of graded domains of dimension two 231 235 244 254 257 264 270

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
160
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(162 citation statements)
references
References 14 publications
2
160
0
Order By: Relevance
“…Hence by the properties of triangles we have h A = f g for a map f : B → τA [1]. This proves what we want.…”
Section: Hom(c D)supporting
confidence: 72%
See 3 more Smart Citations
“…Hence by the properties of triangles we have h A = f g for a map f : B → τA [1]. This proves what we want.…”
Section: Hom(c D)supporting
confidence: 72%
“…If either of these properties holds, then the action of the Serre functor on objects coincides withτ [1].…”
Section: The Map H Is In the Socle Of Hom(c A[1]) As A Left End(a)-mmentioning
confidence: 99%
See 2 more Smart Citations
“…Artin and Stafford have shown that every domain of GK dimension two is isomorphic to a twisted homogeneous coordinate ring [1]. Hence, if H is 3-dimensional regular and g ∈ H 3 is a normal element which is not a zero-divisor, then H/gH must be isomorphic to some B.…”
Section: Geometry Of Homogenized Algebrasmentioning
confidence: 99%